Verification of the cell azimuth based on clustering of sampling point and division of switching quadrant - Feng GAO; Lei LEI; Rilan DU; Feng LI; Tan XU; Yin LI; Xiuyu ZUO (Dianxin kexue)
Engineering data mainly depends on manual maintenance,and the poor accuracy restricts the development of network planning optimization.Aiming at the cell azimuth in engineering data,the simulated azimuth of the cor-responding cell was calculated by using the sampling point clustering algorithm and the switching quadrant partition-ing algorithm by collecting the measurement report data and the switching statistical data of the network management system.By comparing the simulated azimuth angle and the actual azimuth angle,the existing problems were found,which could be used to guide the data updating and engineering rectification.Through the actual verification of the current network,the research method has achieved good application effect.Similarly,the study can be applied to the latitude and longitude of engineering data,which has a strong reference value.